Interlanguage Pragmatics: A Study of the Refusal Strategies of Indonesian Speakers Speaking English - Novy Amarien (TEFLIN, 1997)
Abstract. This is a pilot study investigating the interlanguage pragmatics of the refusal strategies (RSs) of Indonesian Speakers Speaking English (ISSE). The aims of the study are to investigate strategies ISSE use in their refusals of, specifically, offering and requesting initiation acts (IAs). Data were taken from 30 Discourse Completion Tasks undertaken by five males and females in the following groups: Indonesian speakers Speaking Indonesian (ISSI), ISSE and Australian Speakers Speaking English (ASSE). The study revealed that ISSE strategies in refusing offers were `intercultural, that is apparently uninfluenced by L1 patterns and yet not characteristic of L2 patterns. Pragmatic transfer was not in evidence. The data in this study could be the basis for further research in Indonesian interlanguage pragmatics.